Aperiodic Metagratings for High‐Performance Multifunctional Acoustic Lenses. Issue 12 (5th November 2020) - Qian, Jiao; Xia, Jian‐Ping; Sun, Hong‐Xiang; Wang, Yin; Ge, Yong; Yuan, Shou‐Qi; Yang, Yihao; Liu, Xiao‐Jun; Zhang, Baile
Abstract: Metagratings have provided great flexibility for controlling wave propagation by suppressing or enhancing diffraction of periodic unit cells or supercells with high efficiency. On the other hand, to achieve complex wavefront, modulations usually require phase profiles of the metagratings to be arbitrary. However, due to lack of a general theoretical framework, such high‐efficiency aperiodic metagratings remain elusive in reality. Here, a class of aperiodic metagratings based on the extension of the Snell's law that involves both the diffraction of unit cells and the aperiodic phase modulation of metagratings in acoustics is proposed and experimentally demonstrated. The proposed aperiodic acoustic metagratings can be used to not only efficiently manipulate sound refraction or reflection for arbitrary incidence angle without the restriction of critical angles, but also to design complex wavefront modulations that enable high‐performance multifunctional devices. As a proof of concept, two types of multifunctional acoustic lenses that function completely differently by adjusting the distance between two aperiodic metagratings are experimentally realized. This work provides a new pathway toward complex modulations of the wavefront and diffraction for classical waves with high efficiency. Abstract : By considering both the diffraction of unit cells and aperiodic phase modulation, aperiodic acoustic metagratings based on the extension of the Snell's law are proposed and experimentally demonstrated, which can not only efficiently manipulate sound refraction or reflection for arbitrary incidence angles without the restriction of critical angles, but also realize complex wavefront modulations that enable high‐performance multifunctional devices.